Numercial Calculation of Time-varying Meshing Stiffness of Spur Gear based on Weber Energy Method - Yang Changhui; Xu Taojin; Xu Hongbin; Wang Zhiqiang; Liang Juke; Li Bingqian (Jixie chuandong)
Based on the Weber energy method,the numerical integral calculation formula of timevarying meshing stiffness for spur gear is derived.The meshing points are obtained by using the method of variable increment and infinite approximation method.By using this method,the meshing points location of the gear after tooth profile modification can be easily obtained.It is convenient for the study of the tooth profile modification.And by changing the value of the increment,the accuracy errors of the position of the meshing points can be controlled within 10-4 mm.And some MATLAB programs are written to calculate the time-varying meshing stiffness of the first stage planetary spur gear of a high-power wind turbine gearbox,thus it will lay the foundation for the subsequent dynamics analysis of wind turbine gearbox.